COMPARATIVE ANALYSIS OF SENTENCE STRESS IN ENGLISH AND UZBEK (Ideal Journal of Multidisciplinary Research, 2026)
Sentence stress is one of the most important prosodic features in spoken language, playing a significant role in conveying meaning, emphasis, and communicative intention. In both English and Uzbek, sentence stress helps highlight important information within a sentence and contributes to the overall rhythm and intonation of speech. This article presents a comparative analysis of sentence stress in English and Uzbek, examining their structural, functional, and communicative characteristics. The study explores how sentence stress operates in both languages, identifies similarities and differences in stress patterns, and analyzes their role in expressing emphasis and semantic focus. The findings demonstrate that although both languages use sentence stress to emphasize meaningful elements, they differ in rhythmic structure, grammatical influence, and intonational patterns. Understanding these differences is essential for effective communication, language teaching, and translation.
Keywords: sentence stress, prosody, intonation, English language, Uzbek language, phonetics, comparative linguistics.